SOSIALISASI DAN PENDAMPINGAN PEMBUATAN SITE PLAN AGROEDUWISATA SMP BINA HARAPAN JATIGEDE SUMEDANG - Djuwendah, Endah; Yudha, Eka Purna; Karyani, Tuti; Wulandari, Eliana; Saidah, Zumi; Rasmikayati, Elly; Syamsiyah, Nur (Universitas Padjadjaran, 2024)
Mekarasih is one of the pioneering tourist villages in the Jatigede Reservoir Area of Sumedang Regency which has the potential to be managed as an agrotourism village because of its strategic location on the edge of the reservoir and the potential of its natural resources. The problem in this area is the conversion of rice fields into reservoir waters, thereby reducing agricultural activities as a source of livelihood for the population. Therefore, the solution offered is to develop agro-edutourism that combines agricultural and tourism activities. The Binaraja Millenial Smart Farming (BMSF) Community and the management of SMP Bina Harapan Jatigede are an important part of the development of agro-edutourism in Mekarasih village. This community service (PKM) aims to empower communities based on local resources. Community service is carried out through three stages of activity, namely preparation, implementation, monitoring and evaluation. Community service uses lecture methods, FGD, simulations and practice in making a site plan for an agro-edutourism garden located in the SMP Bina Harapan Jatigede area. The results of the activity show that the PKM target partners are able to understand the concept of agro-edutourism, can prepare agro-edutourism planning according to the characteristics of local resource potential and create agro-edutourism site plan designs. It is hoped that the site plan will be used as a basis for planning to build various tourism support facilities based on the concept of sustainable community-based agro-edutourism.Mekarasih merupakan salah satu desa wisata rintisan di Kawasan Waduk Jatigede Kabupaten Sumedang yang potensial dikelola menjadi desa agrowisata karena letaknya yang strategis di pinggir waduk dan potensi sumber daya alam yang dimilikinya. Permasalahan yang ada di wilayah ini adalah terjadinya alih fungsi lahan sawah menjadi wilayah perairan waduk sehingga berkurangnya aktivitas pertanian sebagai sumber mata pencaharian penduduk. Oleh karena itu, solusi yang ditawarkan adalah mengembangkan agroeduwisata yang memadukan aktivitas pertanian dan pariwisata. Komunitas Binaraja Millenial Smart Farming (BMSF) dan pengelola SMP Bina Harapan Jatigede merupakan bagian penting dalam pengembangan agroeduwisata di Desa Mekarasih. Pengabdian pada masyarakat ini bertujuan untuk pemberdayaan masyarakat berbasis sumber daya lokal. Pengabdian dilakukan melalui tiga tahapan kegiatan yaitu persiapan, pelaksanaan, monitoring dan evaluasi. Pengabdian menggunakan metode ceramah, FGD, simulasi serta praktik membuat site plan kebun agroeduwisata yang berada di kawasan SMP Bina Harapan Jatigede. Hasil kegiatan menunjukkan mitra sasaran PKM mampu memahami konsep agroeduwisata, dapat menyusun perencanaan agroeduwisata sesuai dengan karakteristik potensi sumber daya lokal dan membuat rancangan site plan agroeduwisata. Diharapkan nantinya site plan dijadikan sebagai dasar perencanaan membangun berbagai fasilitas penunjang wisata berdasarkan konsep agroeduwisata berbasis masyarakat yang berkelanjutan.